Improving Residents’ Well-being in Low-Cost Housing: An Analysis of Safety and Health Satisfaction. - Amran, Nur Dini Syazwin; Jabar, Izatul laili (Research in Management of Technology and Business, 2025)
The well-being of low-cost housing’s residents in safety and health is a vital issue, however it is often overlooked. This research delves into the residents’ satisfaction in Low-Cost Housing in Shah Alam, focusing on the fundamental aspects in safety and health. This research aims to recommend safety and health improvement to the residents’ wellbeing in low-cost housing. The research methodology involved a multi-phase approach, encompassing the compilation of secondary data through literature review and the collection of primary data by questionnaire surveys and on-site observation. The findings suggest that residents are dissatisfied with certain aspects of safety and health, including safety nets, CCTV, firefighting, parking space, and lighting/illumination. Addressing these concerns through targeted measures will not only improve residents’ safety and health but also contribute to the overall well-being of the community.